Analysis of Location Determination for Temporary Waste Collection Points Using p-dispersion Method: An Application to Yogyakarta City, Indonesia - Donny Dwi Julianto; Annie Purwani; Siham Bouguern (Journal of Novel Engineering Science and Technology, 2023)
The city of Yogyakarta, particularly the Maliobro-Kranggan sector, with a total population of 117,656, has the potential to generate 221 m3/day of waste, while the total capacity of the existing temporary waste collection points or Temporary Disposal Sites (TPS) is 17 units with a capacity of 306 m3. The Yogyakarta Environmental Agency must reconsider the number of TPS facilities and their capacities to meet the community's needs. In certain areas, there are nearby TPS locations, causing some of them not to function optimally as the community chooses the ones that are easily accessible. On the other hand, the proximity of TPS facilities also disturbs the comfort of the community due to worsening odor pollution. In response to this issue, this research aims to determine the optimal number of TPS facilities and their ideal locations using the p-dispersion method. This method is used to determine facility locations by maximizing the minimal distance between each available facility. This research also adds a criterion by considering the travel distance from waste sources to the selected facilities. The study is conducted using Lingo 11.0 software. Based on the data processing results, 13 of 17 TPS facilities were established. The total capacity is 254 m3/day, which can serve as the waste source for 13 community locations. The objective value obtained is 5900, which indicates that the minimum separation distance for the ideal facilities is 5900 meters.